Role of tranexamic acid on blood loss in laparoscopic cholecystectomy - Paras Kumar Pandove; Rachan Lal Singla; Pallavi Mittal; Nikhil Mahajan; Ashwani Kumar (Nigerian Journal of Surgery, 2017)
Context: Nonsurgical uses of tranexamic acid include the management of bleeding associated with leukemia, ocular bleeding, recurrent hemoptysis, menorrhagia, hereditary angioneurotic edema, and numerous other medical problems. However, there is hardly any documentation of the use of tranexamic acid in laparoscopic cholecystectomy. Aims: This study was conducted to evaluate the role of tranexamic acid in limiting blood loss in laparoscopic cholecystectomy and to evaluate the effect of blood loss on morbidity in terms of hospital stay and mortality of the patient. Subjects and Methods: The study was conducted on sixty patients admitted with gallstones, candidates for laparoscopic cholecystectomy. Thirty patients received an intravenous 20 mg/kg bolus dose of tranexamic acid at induction of anesthesia (Group A), and another thirty did not receive the aforementioned drug at induction (Group B). Statistical Analysis: The two groups were compared, and the data collected were entered and tabulated using Microsoft Office Excel and analyzed using appropriate statistical tests. Results: The mean postoperative hospital stay (2.4 vs. 2.63, P = 0.4147), drain fluid hemoglobin (Hb) (0.83 vs. 0.90, P = 0.2087), drain fluid hematocrit (0.2434 vs. 0.2627, P = 0.3787), mean drain output (85 vs. 87.23, P = 0.9271), mean pulse rate at the start of surgery (74.2 vs. 75, P > 0.999), mean pulse rate 24 h after surgery (75.9 vs. 76.4, P = 0.5775), and mean change in Hb (0.240 vs. 0.266, P = 0.2502) in both the groups were not significant. Conclusions: There is no active role of tranexamic acid in elective laparoscopic cholecystectomy.